Mozes F. Heinschink, Daniel Krasa - Lehrbuch des Lovari. Die Romani-Variante der österreichischen Lovara: ed. Dieter W. Halwachs, Barbara Schrammel-LeberHelmut Buske Verlag Hamburg, 2015, 388 s. - Wagner, Peter (Romano džaniben, 2017)
RECENZE